Assessing acute and chronic Staphylococcus aureus growth and virulence in an ex vivo model of cystic fibrosis lung infection. Issue 7 (10th July 2020) - Crealock-Ashurst, Branagh; Harrison, Freya; Sweeney, Esther
Abstract : Staphylococcus aureus is routinely found in sputum samples obtained from people with Cystic Fibrosis (CF). However, its role in the progression of the disease is unclear. This is important, as antibiotic clearance of S. aureus in CF yields unclear clinical results and there is debate around the utility of anti-Staphylococcal antibiotic treatment. We used an ex vivo porcine lung model (EVPL) to compare the growth and virulence of S. aureus isolates from acute CF exacerbations, with isolates from the same donors when they were stable. There was no significant difference in mean bacterial load between donors, strains or clinical state. However, when we compared the variance in bacterial load of each pair of exacerbation/stable isolates across experimental replicates of the lung model, we found that stable samples grew more consistently in the EVPL compared to those taken from the same donor during an exacerbation. Virulence factor assay results were mixed, with results implying greater virulence in either stable or acute samples after passage through the EVPL. We could not detect the AIP quorum sensing signal, which control expression of numerous acute virulence factors, using a reporter assay. We hypothesise that S. aureus might down-regulate Agr expression in the model, consistent with a role as a silent persister, rather than as a pathogenic agent. Further work using the EVPL model will determine how well this reflects the clinical reality in CF.